1999
DOI: 10.1046/j.1471-4159.1999.0722145.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Inhibition of Human Tyrosine Hydroxylase Type 1 Is Controlled by the Specific Portion in the N‐Terminus of the Enzyme

Abstract: Tyrosine hydroxylase (TH), which converts L-tyrosine to L-DOPA, is a rate-limiting enzyme in the biosynthesis of catecholamines; its activity is regulated by feedback inhibition by catecholamine products including dopamine. To investigate the specific portion of the N-terminus of TH that determines the efficiency of dopamine inhibition, wild-type and N-terminal 3 5 , 38-, and 44-amino acid-deleted mutants (del-35, del-38, and del-44, respectively) of human TH type l were expressed as a maltose binding protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…This correlates with data demonstrating that the N-terminus of TH is involved in stabilising the binding of dopamine to the high affinity site [26][27][28]. However, dopamine was still able to bind to the low affinity site of the N-terminal deletion mutant with a K D which approximates that found in the full-length phosphorylated and non-phosphorylated TH [4,7,17].…”
Section: Discussionsupporting
confidence: 87%
“…This correlates with data demonstrating that the N-terminus of TH is involved in stabilising the binding of dopamine to the high affinity site [26][27][28]. However, dopamine was still able to bind to the low affinity site of the N-terminal deletion mutant with a K D which approximates that found in the full-length phosphorylated and non-phosphorylated TH [4,7,17].…”
Section: Discussionsupporting
confidence: 87%
“…The stabilizing conformational changes associated to binding of these compounds are most probably linked to rearrangement of the N-terminal tail of TH, closing the active site [56]. It has been shown that residues 35-41 in the N-terminal tail [41,56,57], as well as residues from the catalytic domain, notably around Ala297 (rat TH numeration), are involved in the stabilizing, inhibitory conformational change effected by dopamine [56,58]. Based on the crystal structure of dopamine bound to the catalytic domain of PAH [59], dopamine would bind to TH in an axial and perpendicular conformation with respect to the length of the active site axis.…”
Section: Discussionmentioning
confidence: 99%
“…dopamine. The enzyme that catalyzes the first step, tyrosine hydroxylase (TH), shows strong substrate inhibition by tyrosine [6][7][8]. The velocity curve for TH as a function of cytosolic tyrosine concentration is shown in Fig.…”
Section: Tyrosine Hydroxylasementioning
confidence: 99%
“…Substrate inhibition of tyrosine hydroxylase (TH) and tryptophan hydroxylase (TPH). The velocity curve for TH as a function of tyrosine concentration is shown using parameters (K m ¼ 46, K i ¼ 160) obtained from fitting data [8]. The velocity curve for THP as a function of tryptophan concentration uses parameters (K m ¼ 46, K i ¼ 400) obtained by fitting experimental curves [12,13].…”
Section: Acetylcholinesterasementioning
confidence: 99%